Physical therapy ethics - Gabard, Donald L., 1946- 4 0 16; 1946- Martin, Mike W.; 5 (Philadelphia, PA : F.A. Davis Company, 2003)
Examines ethical dilemmas that physical therapists frequently encounter, with examples drawn from real-life cases.
Includes bibliographical references and index.
Adult;Adult.
Keywords: 2 -- 0; 6; Professional ethics.;Moral and ethical aspects.;Ethics.;Ethics. -- Physical therapists;Physical therapy;Physical therapists;Physical therapy; 20; 2